Assessment of ovarian reserve in women undergoing cystectomy for benign ovarian disease - Deb, Shilpa (2012)
Ovarian cystectomy is commonly performed to treat benign ovarian cysts, but might cause inadvertent damage to normal ovarian tissue, thereby influencing a woman’s ovarian reserve. Ovarian reserve is defined as the existent quantitative and qualitative supply of follicles which are found in the ovaries that can potentially develop into mature follicles which in effect determine a woman’s reproductive potential. It is commonly quantified by the levels of serum FSH and recently by total antral follicle count (2.0-10.0 mm follicles in both ovaries) and AMH levels. These tests however have inherent biological variation in relation to menstrual cycle and ageing; and are also influenced by the intra- and inter-observer variations. The aim of this thesis was to develop a reliable method of examining the effect of ovarian cystectomy on ovarian reserve.